Nursing of a patient with lumbar disc herniation treated with appropriate Traditional Chinese Medicine techniques based on the theory of strengthening bones and softening tendons (基于“筋柔骨正”理论运用中医适宜技术治疗腰椎间盘突出症1例护理体会) - MA Xiaoyu (马晓玉); DING Fenfang (丁芬芳) (中西医结合护理)
This paper summarizes the nursing experience of treating a patient with lumbar disc herniation using appropriate Traditional Chinese Medicine (TCM) techniques based on the theory of strengthening bones and softening tendons. Based on the theory and TCM syndrome differentiation, auricular acupoint pressing, integrated moxibustion with Huolong cupping therapy, and meridian-dredging and arthralgia-relieving moxibustion were implemented to relieve the low back pain and improve the recovery of lumbar function. Additionally, targeted nursing interventions including syndrome-differentiated dietary, functional exercises, daily life support, and emotional care were carried out to reduce patient’s anxiety and optimize the overall effectiveness of TCM treatment. (本文总结以“筋柔骨正”为理论基础实施中医适宜技术治疗1例腰椎间盘突出症(LDH)患者的护理体会。基于“筋柔骨正”理论, 通过中医辨证, 在患者饮食、情志及功能锻炼方面进行针对性指导, 同时联合耳穴贴压、火龙罐综合灸、循经通痹灸等中医适宜技术, 有效缓解患者疼痛症状, 改善腰部功能, 减轻焦虑, 实现“筋柔软而不强硬、骨正而不曲”的理想治疗效果。)